Challenges of the European Union enlargement: A note from the polish perspective - Grzegorz Gorzelak (Employment and regional development policy: Market efficiency versus policy intervention, 2004)
It is an obvious statement that the first 21st century enlargement of the European Union is a very important and meaningful event, both for the old and the new Member States, their societies and their economies. It is also an obvious statement that for both sides, as well as for the whole of Europe and even for the global political and economic system, and especially for the newcomers, the overall balance of this decision will be - in a long run - a very positive one. However, enlargement has its challenges and dangers, conceived not only in absolute, but also in relative terms. Its positive effects can be smaller or greater, as well as the price both sides would have to pay for achieving the expected results. This note aims at indicating some challenges which face all actors of this new, continental game called enlargement.
hdl:10419/62287; http://EconPapers.repec.org/RePEc:zbw:arlssd:5
Keywords: 330